Pengetahuan dan Sikap Lansia Berhubungan dengan Self Care - Edy Prawoto; Rini Komalawati; Evi Novitasari (Universitas Malahayati Lampung, 2023)
ABSTRACT The age of the elderly can affect the knowledge of the elderly, because as they get older, the ability of the elderly to carry out their activities decreases, including the memory of their knowledge and attitudes. So knowledge of self care is very important because good knowledge can improve the health of the elderly. The purpose of this study was to determine the relationship between knowledge and attitudes of the elderly with self care in Ngujung Village, Magetan Regency. Quantitative research with a Cross Sectional approach, with a population of 355 elderly. The sampling technique used Cluster Random Sampling. The number of samples in the study amounted to 86 elderly people. The research data were analyzed using the Spearman Rank test. The majority of elderly people in Ngujung Village have good knowledge of 81 (94.2%) respondents, the attitudes of the elderly are mostly positive by 61 (76.9%) respondents and the majority of elderly self care is 63 (73.2%) . The results of the Spearman Rank statistical test on knowledge of the elderly with self-care obtained p = 0.005 less than 0.05 with a correlation coefficient of r: 0.302 with a sufficient correlation category and the attitude of the elderly with self-care obtained p = 0.001 less than 0.05 with a correlation coefficient of r: 0.352 with sufficient correlation category. H1 is accepted, it means that there is a relationship between elderly knowledge and self care and there is a relationship between elderly attitudes and self care in Ngujung Village, Magetan Regency. It is expected that the elderly will understand information about the influence of the relationship between knowledge and attitudes of the elderly with self care. Keywords: Knowledge, Attitude, Elderly, Self Care ABSTRAK Umur dapat mempengaruhi pengetahuan lansia, karena seiring bertambahnya usia semakin mengalami penurunan kemampuan lansia melakukan aktivitasnya, termasuk daya ingat dari pengetahuan dan sikap yang dimilikinya. Maka pengetahuan self care sangat penting karena pengetahuan yang baik dapat meningkatkan kesehatan lansia. Tujuan penelitian ini adalah mengetahui Hubungan Pengetahuan dan Sikap Lansia Dengan Self Care Di Desa Ngujung Kabupaten Magetan. Penelitian kuantitatif dengan pendekatan Cross Sectional, dengan jumlah populasi 355 lansia. Teknik sampling menggunakan Cluster Random Sampling jumlah sampel dalam penelitian berjumlah 86 lansia. Data penelitian dianalisis menggunakan uji Rank Spearman. Tingkat Pengetahuan lansia di Desa Ngujung mayoritas memiliki pengetahuan baik sebesar 81 (94,2%) responden, sikap yang dimiliki lansia mayoritas positif sebesar 61 (76,9%) responden dan self care lansia mayoritas sebesar 63 (73,2%). Hasil uji statistic Rank Spearman pada pengetahuan lansia dengan self care diperoleh p = 0,005 kurang dari 0,05 dengan koefisien korelasi r : 0,302 dengan kategori korelasi cukup dan sikap lansia dengan self care diperoleh p = 0,001 kurang dari 0,05 dengan koefisien korelasi r : 0.352 dengan kategori korelasi cukup. H1 diterima berarti ada hubungan pengetahuan lansia dengan self care dan ada hubungan sikap lansia dengan self care di Desa Ngujung Kabupaten Magetan. Diharapkan lansia mengetahui informasi mengenai pengaruh tentang hubungan pengatahuan dan sikap lansia dengan self care. Kata Kunci: Pengetahuan, Sikap, Lansia, Self Care